2015
DOI: 10.4181/rnc.2015.23.02.980.6p
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of functionality and gait in hemiparetic

Abstract: original RESUMOObjetivo. Comparar os efeitos do método Kabat com a estimulação elétrica funcional (FES), bem como a associação dos métodos na capacidade funcional de pacientes hemiparéticos. Método. Trata-se de uma série de casos com três pacientes hemiparéticos. Os participantes foram avaliados ao início e término do tratamento quanto à amplitude de movimento articular de tornozelo, constituintes da marcha e funcionalidade. Os pacientes foram divididos aleatoriamente em: (A) tratado com Kabat; (B) tratado com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“… 11 Some authors suggest a period within three to 30 days post-stroke. 22 , 26 , 27 while others 28 reported that even chronic patients had improvements. 29 These last studies describing “late plasticity” may be the reason why we observed changed electromyographic activation patterns in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Some authors suggest a period within three to 30 days post-stroke. 22 , 26 , 27 while others 28 reported that even chronic patients had improvements. 29 These last studies describing “late plasticity” may be the reason why we observed changed electromyographic activation patterns in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have been reported to exhibit abnormalities in the temporal characteristics of muscle activity compared to normal gait 19 and these changes in IS group maybe an strategy in an attempt to deal with the non-functional gait. 10 , 20 , 21 , 22 As BF muscle helps the hip extension, and ST — RF co-contraction keeps the knee extension during the gait cycle, 4 the anticipation of these three muscles increases the stiffness theses joints in order to help supporting full body weight. Moreover, the weakness of the calf muscles contributes to this.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that stroke rehabilitation is most effective and improves functional outcomes if initiated even early (within three to 30 days post stroke) [21,22]. Paolucci et al [23] assessed the specific influence of the onset-admission interval on rehabilitation results in 145 patients and found that beginning treatment within the first parameters using stabilometric platforms (SPs).…”
Section: Intervention Periodmentioning
confidence: 99%